Acute and chronic caffeine administration differentially alters striatal gene expression in wild-type and adenosine A(2A) receptor-deficient mice. - Dassesse, D; Ledent, C; Parmentier, M; Schiffmann, SN (2001)
In order to assess for the respective involvement of adenosine A(1) and A(2A) receptors (A(2A)-R) in the consequences of short- and long-term caffeine exposure on gene expression, the effects of acute caffeine administration on striatal, cortical, and hippocampal expression of immediate early genes (IEG), zif-268 and arc, and the effects of long-term caffeine or 1,3-dipropyl-8-cyclopentylxanthine (DPCPX) exposure (once daily for 15 days) on striatal gene expression of substance P, enkephalin, and glutamic acid decarboxylase isoforms, GAD65 and GAD67, were evaluated in wild-type and A(2A)-R-deficient (A(2A)-R(-/-)) mice. In situ hybridization histochemistry was performed using oligonucleotides followed by quantitative image analysis. Our results demonstrated that a biphasic response of IEG expression to acute caffeine observed in the wild-type striatum was resumed in a monophasic response in the mutant striatum. In the cerebral cortex and hippocampus, the effect of caffeine was weak in wild-type, whereas in mutant mice it induced a 2-3-fold increase in the IEG expression to restore a level similar to the wild-type basal expression. Chronic caffeine and DPCPX-mediated regulation in neuropeptide and GADs striatal gene expression typically showed the mimicking of alterations resulting from the A(2A)-R genetic deficiency in 25 mg/kg caffeine-treated wild-type mice as well as the dose-dependent normalization of substance P and enkephalin expression in A(2A)-R(-/-) mice. These results indicate that, depending on the dose, the blockade of A(2A)-R or A(1) receptors by caffeine is preferentially revealed leading to highly differential alterations in striatal gene expression and they also suggested the central role of these two receptors on the control of dopaminergic functions.